Răspuns :
Răspuns
Explicație pas cu pas:
9) a) a = - 13
a · b + a = - 182
a · ( b + 1 ) = - 182
( - 13 ) · ( b + 1 ) = - 182
b + 1 = ( - 182 ) : ( - 13 )
b + 1 = 14
b = 14 - 1
b = 13
__________________________________
b) a = - 14
a · b + a · c = + 182
a · ( b + c ) = 182
( - 14 ) · ( b + c ) = 182
b + c = 182 : ( - 14 )
b + c = - 13 → suma
_______________________
c) a = 15
a × b + a × c + 15 × a = - 3 510
a × ( b + c + 15 ) = - 3 510
a × ( 15 + 15 ) = - 3 510
a × 30 = - 3 510
a = ( - 3 510 ) : 30
a = - 117